Potensi Sampah Landfill Mining Di Tpst Bantargebang Sebagai Bahan Baku Alternatif Refused Derived Fuel (RDF) - Imam Rifa'i; Dodit Ardiatma (DPPM Universitas Pelita Bangsa, 2022)
Landfills contain materials that can be taken for recycling or used as an energy source. The purpose of this study was to characterize waste that has long been buried in the landfill which includes composition analysis, proximate analysis, and ultimate analysis. Then the waste is analyzed for its use as recycled material and an energy source. The research was conducted at the Bantargebang TPST. Sampling was carried out on waste that had been buried in landfills by digging at a depth of up to 5 m using an excavator. The samples were then dried in the sun, sieved through a rotary screen, and sorted manually. Some samples were taken by the quartering method for later analysis in the laboratory. The results of the research and analysis show that (i) TPST excavated waste is dominated by compostable materials (31%) and plastic combustible materials (32%) and non-plastic combustibles (26%); (ii) -shaped material such as compost has potential as a substitute for soil cover for landfill and as a soil conditioner; (iii) potentially recyclable materials such as plastic waste need intensive sorting and cleaning; (iv) TPST excavated waste has the potential to be used as an energy source or RDF (refuse-derifed fuels) with a calorific value between 7.31 MJ/kg; (v) TPST excavated waste has the potential to be used as fuel for PLTSa incinerators; (vi) the utilization of TPST excavated waste for the cement industry still faces several obstacles, such as the high chlorine content and water content. Keywords: Landfill, Waste Characterization, Composition, Proximate, Ultimate